Shape Memory Alloy Helical Microrobots with Transformable Capability towards Vascular Occlusion Treatment - Hehua Zhang; Borui Xu; Yi Ouyang; Yunqi Wang; Hong Zhu; Gaoshan Huang; Jizhai Cui; Yongfeng Mei (Research, 2022)
Practical implementation of minimally invasive biomedical applications has been a long-sought goal for microrobots. In this field, most previous studies only demonstrate microrobots with locomotion ability or performing a single task, unable to be functionalized effectively. Here, we propose a biocompatible shape memory alloy helical microrobot with regulative structure transformation, making it possible to adjust its motion behavior and mechanical properties precisely. Especially, towards vascular occlusion problem, these microrobots reveal a fundamental solution strategy in the mechanical capability using shape memory effect. Such shape-transformable microrobots can not only manipulate thrust and torque by structure to enhance the unclogging efficiency as a microdriller but also utilize the high work energy to apply the expandable helical tail as a self-propulsive stent. The strategy takes advantage of untethered manipulation to operate microsurgery without unnecessary damage. This study opens a route to functionalize microrobots via accurate tuning in structures, motions, and mechanical properties.